Bidikmisi Scholarship Selection in UIN Sunan Kalijaga Using Profile Matching Method - Puguh Jayadi; Ahmad Subhan Yazid; Muhammad Mustakim (IJID (International Journal on Informatics for Development), 2016)
An objective process is needed in the selection of Bidikmisi Scholarship in UIN Sunan Kalijaga Yogyakarta, so the selected recipients are not misdirected and meet the established criteria. At present, the process is still manual so it requires a long time and triggers some errors. For this reason, a decision support system is needed to increase the efficiency and effectiveness of the ongoing selection process. The method used is Profile Matching. The method matches the profile of the new registrant with the ideal profile of the scholarship recipient. The matching results will provide recommendations for applicants who are eligible to award Bidikmisi Scholarships. There are 4 aspects used for calculations:  parents, students, house and the interview. From these aspects, it will be divided into 28 criteria with a range of criteria according to the predetermined criteria. System testing is done by Alpha and Beta testing, the results show that the system can function properly as expected. The system provides results as recommendations for candidates through ranking from the final results of system calculations.